The Investigation of HBV Pre-S/S Gene Mutations in Occult HBV Infected Blood Donors with anti-HBs Positive - Yan Guo; Yu Lan; Yuanyuan Jing; Bin Cai; Hanshi Gong; Yixin Zhang; Yong Duan (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. The coexistence of hepatitis B virus (HBV) and hepatitis B surface antibodies (anti-HBs) in occult hepatitis B virus infection (OBI) is a contradictory phenomenon, and the underlying mechanism is not fully understood. The characteristics of pre-S/S mutations in OBI genotypes B and C (OBIB and OBIC) in the presence or absence of anti-HBs were analyzed extensively in this study. Methodology. The amino acid substitutions of envelope proteins of 21 OBI strains, including 4 HBs (+) OBIB, 6 HBs (−) OBIB, 6 HBs (+) OBIc, and 5 HBs (−) OBIC samples, were analyzed and fully compared among groups of HBV genotypes and the presence of anti-HBs. Results. The mutation rates in pre-S1, pre-S2, and S proteins of OBIC were significantly higher than wild-type HBV (wt-HBV) genotype C strains, but only the mutation rate of S protein in OBIB was significantly higher compared to wild-type HBV genotype B. The mutation rates in S protein of anti-HBs (−) OBI were higher than anti-HBs(+) OBI samples (4.40% vs. 2.43% in genotype B, P>0.05; 6.81% vs. 3.47% in genotype C, P<0.05). For these high-frequency substitutions in the pre-S/S region, the mutations sN40S and sK122R were found in 27.3% and 45.5% of anti-HBs (−) OBI strains, respectively. 7 substitutions were uniquely found in OBIC strains and 9 substitutions were commonly detected in OBIB and OBIC strains. Conclusions. These results suggested that the mutations might occur randomly and were not selected by antibody pressure.